STRATEGY OF MAINTAINING CUSTOMER LOYALTY WITH SATISFACTION AS INTERVENING VARIABLE AT COFFEE SHOP UNDERPASS GRESIK - Woro Utari; Nurus Sobakh; Melyana Arta Sari Sirait; Waras Waras (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2023)
This study aims to examine and analyze the effect of service quality and trust on customer loyalty. The sampling technique used in this study was non-probability sampling, namely accidental sampling with a total of 100 respondents. The data analysis technique in this study uses hypothesis testing using path analysis or what is called Path Analysis with the help of the SPSS version 20 program. The type of data used in this study is questionnaire / questionnaire data. The results of this study indicate that service quality has a significant effect on satisfaction but has no significant effect on loyalty, trust has a significant effect on loyalty, and satisfaction has a significant effect on customer loyalty. However, in the indirect test, service quality has a significant indirect effect on customer loyalty through satisfaction, and trust does not directly affect customer loyalty through satisfaction.